ANALISIS POLA TATA RUANG DAN ELEMEN ARSITEKTUR PADA RUMAH ADAT SUMATERA BARAT (Studi kasus : Anjungan Sumatera Barat, Jakarta Timur) - Fairuz, Farah; Zefri (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2022)
Traditional Minangkabau architecture has its own distinctiveness and characteristics both in architecturalform and philosophy. The building form has a close relationship with the socio-cultural setting of thecommunity. The characteristics of a building can be reviewed through a rationalistic qualitative methodbased on topological, morphological and typological theories. Elements of traditional architecture can becharacteristic of an area. Thus, each work created really has a strong and distinctive foundation, both interms of structure, facade shape, spatial layout and also the use of ornaments. The distinctive and specificform is able to display a form that is in harmony with its environment so that it can remind people or thecommunity of an environment. This form makes Minangkabau architecture easy to remember and recognizeanywhere because whatever is made has a strong foundation and is truly distinctive.